Assessment of Knowledge, Behaviour and Sun Protection Practices among Health Services Vocational School Students - Yurtseven, Eray (MDPI, 2012)
There has been a significant increase in the cases of skin cancer throughout the world in the last few decades. Although the mortality rate of skin cancer is relatively low, its impact on other health aspects is high and the treatment of undesired aesthetic damage is costly. According to disability-adjusted life year rates (DALY), 1.5 million days are estimated to be lost from people’s lives every year worldwide due to ultraviolet (UV) radiation. The purpose of this study was to raise sun health awareness levels among health services vocational school students. A total of 414 students were included in the analysis. A questionnaire form was used to evaluate knowledge, attitudes and behaviours among the survey sample. The average level of knowledge concerning the effects of the sun was found to be 8.64 ± 2.5 out of 15 points. All socio-demographic factors were analysed, but the only significant variables found were age and the possible presence of skin cancer within the immediate family (p < 0.05).